2018
DOI: 10.1016/j.ijrmms.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Micro-damage evolution and macro-mechanical property degradation of limestone due to chemical effects

Abstract: This is a repository copy of Micro-damage evolution and macro-mechanical property degradation of limestone due to chemical effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 32 publications
(35 reference statements)
0
21
0
Order By: Relevance
“…7d, e. Samples of other pHsolutions are not shown because their damage evolution is similar. Under the effect of external compressive stresses the micro damage of limestone can be divided into four stages (Li et al 2018), as shown in Fig. 7a-c, which also has a close relationship with the permeability changes of the rock sample.…”
Section: The Relationship Between the Mechanical Behavior And The Micmentioning
confidence: 98%
See 2 more Smart Citations
“…7d, e. Samples of other pHsolutions are not shown because their damage evolution is similar. Under the effect of external compressive stresses the micro damage of limestone can be divided into four stages (Li et al 2018), as shown in Fig. 7a-c, which also has a close relationship with the permeability changes of the rock sample.…”
Section: The Relationship Between the Mechanical Behavior And The Micmentioning
confidence: 98%
“…6 are the thresholds of the permeability evolution under unloading condition; before this point, the permeability decreases slightly, and after that begins to increase. The inflection points indicate the samples are already fully compacted; after these points, micro cracks begin to form some interconnections amongst them (Li et al 2018). The mechanism governing changes in the permeability of chemically corroded limestone samples under external stress is discussed in Sect.…”
Section: Hydrochemical-mechanical Effects On Permeability Changes Of mentioning
confidence: 99%
See 1 more Smart Citation
“…e corresponding chemical damage model was established. Liu et al [21][22][23][24][25][26] took the sandstone in the ebb-flow zone of a reservoir in the ree Gorges as the research object.…”
Section: Introductionmentioning
confidence: 99%
“…ey summarized the changing law of mechanical properties and macro-and microdamage mechanisms of sandstone under dry-wet cycles [21,22] as well as the change of the physical parameters and microdamage mechanisms of limestone under chemical solution immersion. ey found that the basic reason for the decline of the mechanical properties of rocks was that the pH value of the chemical solution changed the porosity and microdamage evolution of the rocks [23]. In addition, they also analyzed the deterioration rule of sandstone mechanical parameters under acid-base conditions [24,25] and developed a numerical simulation program based on an improved Duncan-Chang constitutive model [26].…”
Section: Introductionmentioning
confidence: 99%